Helminthosporium velutinum and H. aquaticum sp. nov. from aquatic habitats in Yunnan Province, China - Zhu, Dan; Luo, Zong-Long; Baht, Darbhe Jayarama; Mckenzie, Eric.h.c.; Bahkali, Ali H.; Zhou, De-Qun; Su, Hong-Yan; Hyde, Kevin D. (Phytotaxa, 2016)
Helminthosporium species from submerged wood in streams in Yunnan Province, China were studied based on morphology and DNA sequence data. Descriptions and illustrations of Helminthosporium velutinum and a new species H. aquaticum are provided. A combined phylogenetic tree, based on SSU, ITS and LSU sequence data, place the species in Massarinaceae, Pleosporales. The polyphyletic nature of Helminthosporium species within Massarinaceae is shown based on ITS sequence data available in GenBank.